Peran Perempuan Dalam Melahirkan Generasi Yang Berkualitas Perspektif Al-Qur’an - Roziardiansyah Roziardiansyah; jatim jatim (STAI Al-Mujtama Pamekasan, 2022)
In the modern era like today, there are many women who work outside the home to meet the needs of their family life, earn a living as an addition to their husband's income, because of the demands of the new era in a society that is experiencing a period of women's emancipation. For women who work will divide attention to work and their families. This is a challenge for women when carrying out multiple roles. This causes many women to be unable to carry out their duties and responsibilities properly in the family, because mothers never know how to properly educate their children, such as being busy with their careers to handing over the biggest responsibility in children's education to the school or child caretaker. his son. As a result of that, how many families are destroyed because mothers are reluctant to educate their children, because they just ignore them, which eventually gives birth to a generation that cannot be expected, namely a generation that is not qualified. Based on the problems above, the researcher will examine more deeply about